Site-specific chemical modification of B-Z junctions in supercoiled DNA as detected by nuclease S1 digestion, inhibition of restriction cleavage and nucleotide sequencing - Nejedlý, K; Matyásek, R; Palecek, E (Journal of biomolecular structure & dynamics, 1988)
Structural distortions on the boundary between right-handed and left-handed segments in the superhelical plasmid pPK2 (a derivative of pUC19 containing (dC-dG)n segments cloned into polylinker) were studied by means of chemical probes. Strong osmium tetroxide, pyridine (Os,py) modification of DNA at native superhelical density (sigma) was found in four thymines surrounding the (dC-dG)13 segment. These results correlated with restriction cleavage inhibition (due to modification): BamHI cleavage was strongly inhibited, unlike the neighbouring XbaI and SalI (weak or no inhibition). In the (dC-dG)8 segment considerably weaker modification of the B-Z junctions was observed, accompanied by weak inhibition of BamHI cleavage, while the neighbouring SmaI and KpnI were not affected. Os,py modification of DNA at native sigma was not detected by nuclease S1 cleavage at and (dC-dG)n segment. However, this enzyme recognized and cleaved at the B-Z junction, osmium modified at more negative sigma. The results obtained with the glyoxal and diethyl pyrocarbonate modification support the idea of very narrow B-Z junctions at native sigma.
Keywords: Electrophoresis, Polyacrylamide Gel; Base Sequence; oxid osmičelý; Restriction Mapping; Deoxyribonucleases, Type II Site-Specific; Single-Strand Specific DNA and RNA Endonucleases; DNA, Superhelical; Molecular Sequence Data; deoxyribonukleasa BamHI; superhelikální DNA; molekulární sekvence - údaje; plazmidy; Osmium Tetroxide; restrikční endonukleasy typu II; sekvence nukleotidů; Deoxyribonuclease BamHI; Plasmids; elektroforéza v polyakrylamidovém gelu; restrikční mapování; endonukleasy specifické pro jednořetězcové nukleové kyseliny